Synthesis, Characterization, and Antibacterial Activity of Plant-Derived Zinc Oxide Nanostructure Using Lavandula angustifolia and Phyllanthus niruri Extracts - Fakhirah, Dhiya; Magfira, Tya Aisha; Hutama, Aulia Sukma; Septama, Abdi Wira; Maryani, Faiza; Krismastuti, Fransiska Sri Herwahyu (Universitas Gadjah Mada, 2024)
In recent years, green synthesized nanomaterials have garnered wide interest due to its inherent features like rapidity, cost-effectiveness, and environmentally friendly technique. The green synthesis of Zinc oxide nanostructures (n-ZnO) using two kinds of plant extract, lavender (Lavandula angustifolia) and meniran (Phyllanthus niruri), were discussed and their antibacterial activities were compared. Characterization by means of X-ray diffraction (XRD), Fourier transform infrared (FTIR), and field emission-scanning electron microscopy/energy dispersive X-ray spectroscopy (FE-SEM/EDS) were used to confirm the successful formation of n-ZnO using both plant extracts. The antibacterial activity of the n-ZnO synthesized from two different plant extracts was tested against Klebsiella pneumoniae and methicillin-resistant Staphylococcus aureus (MRSA). The results show that both n-ZnO has antibacterial activity against MRSA. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values for n-ZnO synthesized from meniran extract were 78 and 156 mg/mL, respectively, while MIC and MBC values for n-ZnO synthesized from lavender extract were 156 and 312 mg/mL, respectively. These results confirm that the n-ZnO prepared from meniran extract is more effective in inhibiting MRSA than the n-ZnO prepared from lavender extract. This study proves that plant-based n-ZnO has anti-microbial activities and may serve as antimicrobial therapeutics.